Pendampingan Dan Pengembangan Manajemen Pemasaran Dapoer Cesky Melalui Strategi Branding - Devi Putri Pratama; Lia Nirawati (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2023)
Micro, Small and Medium Enterprises (MSMEs) are business activities carried out by individuals or groups that aim to prosper individuals and groups. One of the problems faced by MSMEs Dapoer Cesky is a lack of knowledge and understanding of the benefits of branding, they do not have a good entrepreneurial spirit and they have not received training or assistance regarding technical branding strategies. Assistance and development through product re-branding is carried out in several steps, namely surveys and designing logos and supergraphics. It is important for MSMEs players to understand that the branding of a product is the single most important factor to ensure its successful use by the general public or other target markets. This is because according to marketing techniques, branding functions as a means to evoke positive consumer perceptions.